2018
DOI: 10.1101/432351
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Experimental co-transmission of simian immunodeficiency virus (SIV) and the macaque homologs of the Kaposi sarcoma-associated herpesvirus (KSHV) and Epstein-Barr virus (EBV)

Abstract: Macaque RFHV and LCV are close homologs of human KSHV and EBV, respectively. No experimental model of RFHV has been developed due to the lack of a source of culturable infectious virus. Screening of macaques at the Washington National Primate Research Center detected RFHV in saliva of SIV-infected macaques from previous vaccine studies. A pilot experimental infection of two naïve juvenile pig-tailed macaques was initiated by inoculation of saliva from SIV-infected pig-tailed and cynomolgus macaque donors, whic… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 76 publications
0
2
0
Order By: Relevance
“…Accordingly, KSHV persistence is predominantly observed in mice with reconstituted human im-mune system components (humanized mice) in the presence of EBV, and these dual-infected mice develop PEL-like tumors (McHugh et al, 2017). In good agreement, EBV and KSHV orthologs are also co-transmitted in monkeys (Bruce et al, 2018), KSHV is primarily found in co-existence with EBV in Cameroonian children (Labo et al, 2019), and EBV supports persistence of B cell infection by KSHV in vitro (Faure et al, 2019). Moreover, the high prevalence of EBV in the adult human population (>95%) makes it likely that KSHV co-exists in the presence of EBV in most adult individuals (Dunmire et al, 2018).…”
Section: Introductionmentioning
confidence: 86%
“…Accordingly, KSHV persistence is predominantly observed in mice with reconstituted human im-mune system components (humanized mice) in the presence of EBV, and these dual-infected mice develop PEL-like tumors (McHugh et al, 2017). In good agreement, EBV and KSHV orthologs are also co-transmitted in monkeys (Bruce et al, 2018), KSHV is primarily found in co-existence with EBV in Cameroonian children (Labo et al, 2019), and EBV supports persistence of B cell infection by KSHV in vitro (Faure et al, 2019). Moreover, the high prevalence of EBV in the adult human population (>95%) makes it likely that KSHV co-exists in the presence of EBV in most adult individuals (Dunmire et al, 2018).…”
Section: Introductionmentioning
confidence: 86%
“…Interestingly, KSHV infection only persists in humanized mice upon co-infection with EBV ( 23 , 38 ). Similarly, both viruses or their monkey orthologues seem to be co-transmitted in both macaques and humans ( 39 , 40 ). Furthermore, EBV supports KSHV infection of B cells in vitro ( 41 ).…”
Section: Virus Associated Malignanciesmentioning
confidence: 99%